Board monitoring and firm performance: evidence from the UK - Hanafy, Asmaa (AUC Knowledge Fountain, 2020)
There are several research papers regarding the relationship between corporate governance and firm performance. One of the aspects of corporate governance is the board of directors. Board monitoring is a critical aspect which can be measured by number of board meetings and number of board committees. There are several studies on board diversity and composition of board of directors and firm performance, while there are few research studies on the number of board committees and board meetings and their relationship with the firm performance. Accordingly, this thesis focuses on the relationship between board monitoring measured by number of board meetings and number of board committees and firm performance in the UK. The sample is Financial Times and London Stock Exchange (FTSE) 150 which includes the largest 150 listed companies on London Stock Exchange. Firm performance is measured by an accounting measure which is return on assets (ROA) and a market performance measure which is Tobin's Q. The results of this study show that there is no significant relationship between number of board meetings and firm performance. However, there is a significant negative relationship between number of board committees and firm performance. Keywords: board committees, board meetings, corporate governance, firm performance, FTSE150, UK.